A small-angle scattering environment for in situ ultrasound studies. Issue 25 (13th June 2018) - Li, David S.; Lee, Yi-Ting; Xi, Yuyin; Pelivanov, Ivan; O'Donnell, Matthew; Pozzo, Lilo D.
Abstract : We designed and tested a calibrated ultrasound sample environment for in situ small-angle X-ray and neutron scattering measurements. Abstract : Ultrasonic devices are common tools in laboratory and industrial settings to produce cavitation events for cleaning, emulsification, cell lysis and other materials applications. Effects of sonication at the macroscopic scale can be visible while effects at the molecular and nano-scales are not easily probed and, therefore, not fully understood. We present a new small angle scattering sample environment designed specifically to study structural changes occurring in various types of dispersions at the nano-scale due to ultrasonic acoustic waves. The sample environment features two face-to-face high-intensity focused ultrasound transducers coaxially aligned and normal to the neutron/X-ray beam propagation direction. A third broadband transducer is fixed beneath the scattering volume to acoustically monitor for cavitation events. By correlating acoustic data to scattering data, measured structural changes can be correlated to changes in parameters such as frequency, acoustic pressure, or cavitation pressure threshold. Several example applications of colloidal systems effectively influenced by ultrasound fields are also presented to demonstrate the capabilities of the device and to motivate future work on in situ scattering analysis of ultrasound materials processing methods.